Acquisition of Drug Resistance and Dependence by Prions - Oelschlegel, Anja M. (Public Library of Science, 2013)
We have reported that properties of prion strains may change when propagated in different environments. For example, when swainsonine-sensitive 22L prions were propagated in PK1 cells in the presence of swainsonine, drug-resistant variants emerged. We proposed that prions constitute quasi- populations comprising a range of variants with different properties, from which the fittest are selected in a particular environment. Prion populations developed heterogeneity even after biological cloning, indicating that during propagation mutation-like processes occur at the conformational level. Because brain-derived 22L prions are naturally swainsonine resistant, it was not too surprising that prions which had become swa sensitive after propagation in cells could revert to drug resistance. Because RML prions, both after propagation in brain or in PK1 cells, are swainsonine sensitive, we investigated whether it was nonetheless possible to select swainsonine-resistant variants by propagation in the presence of the drug. Interestingly, this was not possible with the standard line of PK1 cells, but in certain PK1 sublines not only swainsonine-resistant, but even swainsonine-dependent populations (i.e. that propagated more rapidly in the presence of the drug) could be isolated. Once established, they could be passaged indefinitely in PK1 cells, even in the absence of the drug, without losing swainsonine dependence. The misfolded prion protein (PrP(Sc)) associated with a swainsonine-dependent variant was less rapidly cleared in PK1 cells than that associated with its drug-sensitive counterpart, indicating that likely structural differences of the misfolded PrP underlie the properties of the prions. In summary, propagation of prions in the presence of an inhibitory drug may not only cause the selection of drug-resistant prions but even of stable variants that propagate more efficiently in the presence of the drug. These adaptations are most likely due to conformational changes of the abnormal prion protein.